Host immune response mediates changes in cagA copy number and virulence potential of Helicobacter pylori - Sungil Jang (Gut Microbes, 2022)
Helicobacter pylori is the major risk factor for gastric cancer. H. pylori harboring the type IV secretion system (T4SS) and its effector CagA encoded on the cag pathogenicity Island (cagPAI) increases the risk. H. pylori PMSS1 has a multi-cagA genotype, modulating cagA copy number dynamically from zero to four copies. To examine the effect of the immune response on cagA copy number change, we utilized a mouse model with different immune status. PMSS1 recovered from Rag1−/− mice, lacking functional T or B cells, retained more cagA copies. PMSS1 recovered from Il10−/− mice, showing intense inflammation, had fewer cagA copies compared to those recovered from wild-type mice. Moreover, cagA copy number of PMSS1 recovered from wild-type and Il10−/− mice was positively correlated with the capacity to induce IL-8 secretion at four weeks of infection. Since recombination in cagY influences T4SS function, including CagA translocation and IL-8 induction, we constructed a multiple linear regression model to predict H. pylori-induced IL-8 expression based on cagA copy number and cagY recombination status; H. pylori induces more IL-8 secretion when the strain has more cagA copies and intact cagY. This study shows that H. pylori PMSS1 in mice with less intense immune response possess higher cagA copy number than those infected in mice with more intense immune response and thus the multi-cagA genotype, along with cagY recombination, functions as an immune-sensitive regulator of H. pylori virulence.